A global dataset on subgrid land surface climate (2015–2100) from the Community Earth System Model. Issue 2 (5th April 2022) - Zhang, Keer; Lee, Xuhui; Schultz, Natalie M.; Zhao, Lei; He, Chunyang; Huang, Qingxu; Liu, Zhifeng; Chu, Haoran; Zhao, Jiayu
Abstract: Subgrid data from earth system models are a powerful, yet underutilized, data resource for investigating the climatic impacts of land use and land cover change (LULCC). In this paper, we describe a global dataset on subgrid land surface climate variables produced by the Community Earth System Model in a fully coupled mode. The simulation was conducted at a 0.9° × 1.25° resolution under the Representative Concentration Pathway (RCP) 8.5 scenario from 2015 to 2100. Data are archived for eight subgrid tiles (urban, rural, tree, grass, shrub, bare soil, crop and lake) and include variables on the physical state, surface energy fluxes, runoff and atmospheric forcing conditions. Archival intervals are monthly, daily and hourly. Meta data on land surface parameters are also available. The data files are stored in NetCDF‐4 (Network Common Data Form, version 4) format and the meta data follow the latest Coupled Model Intercomparison Project phase 6 standards. We anticipate that this dataset will become a useful resource for characterizing local climate changes due to LULCC. This dataset can be downloaded from the Harvard Dataverse (https://doi.org/10.7910/DVN/HUXAH6 ). Abstract : Here, we describe a global dataset on subgrid land surface climate variables produced by the Community Earth System Model under the RCP 8.5 scenario from 2015 to 2100. Data are archived for eight subgrid tiles (urban, rural, tree, grass, shrub, bare soil, crop and lake) and include variables on the physical state, surface energy fluxes, runoff and atmospheric forcing conditions at monthly, daily and hourly intervals. Meteorologists, hydrologists and ecologists can use this dataset to investigate the interplay between surface climate, ecosystem functions and climate change.